Sudden cardiac arrest as a rare presentation of myxedema coma: case report - Divya Salhan; Deepak Sapkota; Prakash Verma; Saroj Kandel; Omar Abdulfattah; Antony Lixon; Deribe Zwenge; Frances Schmidt (Greater Baltimore Medical Center, 2017)
Myxedema coma is a decompensated hypothyroidism which occurs due to long-standing, undiagnosed, or untreated hypothyroidism. Untreated hypothyroidism is known to affect almost all organs including the heart. It is associated with a decrease in cardiac output, stroke volume due to decreased myocardial contractility, and an increase in systemic vascular resistance. It can cause cardiac arrhythmias and the most commonly seen conduction abnormalities are sinus bradycardia, heart block, ventricular tachycardia, and torsade de pointes. The authors report a case of an elderly man who presented with sudden cardiac arrest and myxedema coma and who was successfully revived.